1995
DOI: 10.1111/j.1651-2227.1995.tb13567.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of two infant formulas and human milk on the development of the faecal flora in newborn infants

Abstract: The establishment of the faecal flora of 39 full-term infants fed exclusively on breast milk (n = 20) or with two different modern adapted cow's milk formulas (n = 19) was studied during the first 3 months of life. One formula investigated was based on 100% bovine casein as the protein source whereas the other formula contained bovine milk proteins with a whey/casein ratio of 60:40. A faecal flora rich in bifidobacteria was found in all study groups; the growth of putrefactive bacteria (especially Bacteroides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
113
1
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(130 citation statements)
references
References 21 publications
13
113
1
3
Order By: Relevance
“…The dot blot analysis con rmed our nding that two breast-fed infants, coded 1 and 52, and one formula-fed infant, coded 49 were not colonised by bi dobacteria at the age of 1 and:or 7 months (31). Our results are in line with several studies that show equal, either high (7,8) or low (9,13,27), frequency of bi dobacterial colonisation in both groups. Previous observations that the bi dobacterial populations of infants generally consist of one to three species (30,32,33) are con rmed by our ndings.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The dot blot analysis con rmed our nding that two breast-fed infants, coded 1 and 52, and one formula-fed infant, coded 49 were not colonised by bi dobacteria at the age of 1 and:or 7 months (31). Our results are in line with several studies that show equal, either high (7,8) or low (9,13,27), frequency of bi dobacterial colonisation in both groups. Previous observations that the bi dobacterial populations of infants generally consist of one to three species (30,32,33) are con rmed by our ndings.…”
Section: Discussionsupporting
confidence: 82%
“…H owever, several other culture based studies have shown that both groups of infants have equal frequency and level of bi dobacterial colonisation by the age of approximately 1 month or earlier (7)(8)(9). Con icting results have also been obtained regarding other groups of bacteria such as Bacteroides, clostridia, enterococci, lactobacilli and enterobacteria in breast-fed and formula-fed infants.…”
Section: Introductionsupporting
confidence: 49%
“…In infants it is thought that those who are breast-fed have a natural predominance of bifidobacteria, and also specific strains of bifidobacteria. The formula-fed infants have a microbiota that is more complex and similar to the adults' microbiota, containing bifidobacteria, enterobacteria, lactobacilli, bacteroides, clostridia and enterococci (Benno and Mitsuoka, 1986;Kleessen et al, 1995). After weaning, the composition of the microbiota resembles that of the adult (Edwards, 1993).…”
Section: Development Of Intestinal Microbiotamentioning
confidence: 94%
“…The fluctuation of fecal bacterial populations of neonates has been well established, especially in humans [11,12,21]. However, little is known about the day to day evolution of the composition of intestinal microbiota from the suckling period to maturity.…”
Section: Discussionmentioning
confidence: 99%